The Relationship Between Image Reading Skills and Visual Perception Among Students of the Art Education Department - Fatima Jabbar Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
among students of the Art Education Department in the Colleges of Basic Education. It seeks to understand how visual perceptual levels influence students’ capacity to interpret and analyze visual content within artistic contexts. The researcher adopts a descriptive-analytical methodology with a mixed-methods approach. The research population consisted of Art Education students, and the sample included 180 male and female students during the 2024–2025 academic year, ensuring curricular homogeneity. Data were collected through a standardized Visual Perception Scale and an Image-Reading Skills Test, both designed with purely artistic content to link cognitive processing with creative analysis.Statistical analysis revealed a strong positive correlation ($r = 0.78, p < 0.001$) between visual perception levels and image-reading skills. The findings indicate that students who achieved higher scores on the visual perception scale demonstrated significantly better performance on the test for interpreting artistic elements, understanding compositional relationships, and analyzing symbolic content. The research concludes that visual perception constitutes a fundamental cognitive basis that influences the development of advanced image-reading competencies, which demands a recommendation to enhance and support it sensory and visually within art education contexts.DOI: https://doi.org/10.54633/2333-025-058-018